Theileria parva sporozoite invasion and development within bovine dendritic cells - Wells, C.W.; Awino, Elias; McKeever, Declan J. (Microscopic Society of Southern Africa, 2000)
Theileria parva, an obligate intracellular protozoan parasite of cattle, causes East Coast fever, a fatal, lymphoproliferative disease, endemic in large areas of East and Central Africa. The mammalian-infective sporozoites of T. parva mature within the salivary glands of the ixodid tick Rhipicephalus appendiculatus diculatus and are inoculated into the host during feeding. Sporozoites invade T and B cells and dendritic cells (DC). Mode of entry into these cell types appears very similar. However, studies of the subsequent parasite Development have been confined largely to lymphocytes. Dendritic cells are a feature of bovine dermis and are present in large numbers at the site of tick attachment in cattle. These cells are believed to migrate via the afferent lymphatics to the draining lymph node, where they differentiate into interdigitating dendritic cells within the paracortex. Dendritic cells collected from bovine afferent lymph have been shown to take up large numbers of sporozoites in vitro. Since proliferation of infected lymphoblasts is first observed in the lymph node that drains the site of inoculation, we have characterised sporozoite invasion and differentiation in bovine dendritic cells with a view to evaluating their role in the establishment of infection. This paper summarises Theileria parva sporozoite invasion and Development within bovine dendritic cells. Sporozoites within the cytoplasm of a dendritic cell is illustrated.